Fair Wages and Human Capital Accumulation in a Global Economy - Udo Kreickemeier (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper analyzes trade in an asymmetric 222 world, where the two countries, labelled America and Europe, differ in their attitudes towards wage inequality. In both America and Europe, fair wage considerations compress differentials between the wages for skilled and unskilled workers, leading to involuntary unemployment of unskilled workers in equilibrium. European workers are more averse to wage inequality than American workers though, and as a consequence Europe is characterised by lower wage differentials as well as higher unemployment. Allowing for endogenous skill formation in both countries, the effects of a globalization shock - modelled as the entry of newly industrializing countries into the trading world - on prices and employment levels are derived.
Keywords: 330; globalization; globalisation; unemployment; fair wages; skill upgrading